Core Metabolic Features and Hot Origin of Bathyarchaeota. (June 2019) - Feng, Xiaoyuan; Wang, Yinzhao; Zubin, Rahul; Wang, Fengping
Abstract: The archaeal phylum Bathyarchaeota comprises highly diversified subgroups and is considered to be one of the most abundant microorganisms on earth. The metabolic features and evolution of this phylum still remain largely unknown. In this article, a comparative metabolic analysis of 15 newly reconstructed and 36 published metagenomic assembled genomes (MAGs) spanning 10 subgroups was performed, revealing the core metabolic features of Bathyarchaeota—namely, protein, lipid, and benzoate degradation; glycolysis; and the Wood–Ljungdahl (WL) pathway, indicating an acetyl-CoA-centralized metabolism within this phylum. Furthermore, a partial tricarboxylic acid (TCA) cycle, acetogenesis, and sulfur-related metabolic pathways were found in specific subgroups, suggesting versatile metabolic capabilities and ecological functions of different subgroups. Intriguingly, most of the MAGs from the Bathy-21 and -22 subgroups, which are placed at the phylogenetic root of all bathyarchaeotal lineages and likely represent the ancient Bathyarchaeota types, were found in hydrothermal environments and encoded reverse gyrase, suggesting a hyperthermophilic feature. This work reveals the core metabolic features of Bathyarchaeota, and indicates a hot origin of this archaeal phylum.